Using our whole selves: our experiences with reflexivity while researching a community arts-based leisure program. Issue 4 (1st October 2016) - Genoe, M. Rebecca; Liechty, Toni
ABSTRACT: Although reflexivity is commonly used in qualitative research, how it is used is rarely acknowledged. Multiple definitions and approaches result in a lack of clarity regarding reflexivity. We actively engaged in a reflexive process as we explored the transition of an arts-based leisure program from public to private service provision. We journaled about our positions, thoughts, and emotions throughout the research process. We analyzed our journals through initial and focused coding. Emerging themes included the impact of our positions on the research, the impact of our experiences with the program on our research, role negotiation, emotions related to role blending, and challenges with reflexivity. We report our experiences with reflexivity and explore how it affected our collaborative research process. We offer several recommendations for researchers to consider when embarking on their own reflexive processes.